The Effect of The Number of Departure Passenger on The Quality of Custumer Service Officer (CSO) at Kualanamu International Airport, Medan - Aura P. C., Rahma; Dewi Kusumayati, Lusiana; Olieve, Arnaz (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The Covid-19 pandemic, which is getting better accompanied by less stringent rules for flight service users, has also had an impact on the increasing number of passengers. This study aims to determine whether the number of departing passengers has an effect on the quality of Customer Service Officer (CSO) service at Medan’s Kualanamu International Airport. The research method used is simple linear regression analysis. Determination of the sample was taken with a total of 10 Customer Service Officers (CSO). The data collection technique uses an assessment score form by the customer service supervisor then the data will be processed using a simple linear regression analysis test using the Statistical Package for the Social Sciences (SPSS) application. Based on the calculation results, a significant number of F count is 0.000 <0.05 and the R Square value is 0.961 which implies that the effect of variable X (number of passengers) on variable Y (quality of service of customer service officers (CSO)) is 96.1%. The results of the simple regression equation are Y = 1,065,632.914 – 10,269.492X, which means that the number of passengers has a negative influence on the quality of Customer Service Officer (CSO) service at Kualanamu International Airport, Medan. Customer Service Officer (CSO) can improve and maintain the quality of service provided to passengers without being affected by the large number of passengers.